Senescent epithelial cells remodel the microenvironment for the progression of oral submucous fibrosis through secreting TGF-β1 - Wang, Zijia; Han, Ying; Peng, Ying; Shao, Shuhui; Nie, Huanquan; Xia, Kun; Xiong, Haofeng; Su, Tong (PeerJ, 2023)
Objectives Cellular senescence is strongly associated with fibrosis and tumorigenesis. However, whether the epithelium of oral submucous fibrosis (OSF) undergoes premature senescence remains unclear. This study investigates the roles of senescent epithelial cells in OSF. Methods The immunohistochemistry and Sudan black B staining were performed to identify epithelium senescence in OSF tissues. Arecoline was used to induce human oral keratinocytes (HOKs) senescence. The cell morphology, senescence-associated β galactosidase activity, cell counting Kit 8, immunofluorescence, quantitative real-time PCR, and western blot assay were used to identification of senescent HOKs. The enzyme-linked immunosorbent assay was exerted to evaluate the levels of transforming growth factor β1 (TGF-β1) in the supernatants of HOKs treated with or without arecoline. Results The senescence-associated markers, p16 and p21, were overexpressed in OSF epithelium. These expressions were correlated with alpha-smooth actin (α-SMA) positively and proliferating cell nuclear antigen (PCNA) negatively. Moreover, Sudan black staining showed that there was more lipofuscin in OSF epithelium. In vitro, HOKs treated with arecoline showed senescence-associated characteristics including enlarged and flattened morphology, senescence-associated β galactosidase staining, cell growth arrest, γH2A.X foci, upregulation of p53, p21, and TGF-β1 protein levels. Moreover, senescent HOKs secreted more TGF-β1. Conclusions Senescent epithelial cells are involved in OSF progression and may become a promising target for OSF treatment.
Keywords: Oral submucous fibrosis; Epithelial cell; Cellular senescence; Senescence-associated secretory phenotype; Transforming growth factor β